Management in the industrial world : an international analysis - Harbison, Frederick; Princeton University; Myers, Charles Andrew; Massachusetts Institute of Technology (New York, McGraw-Hill, 1959)
This volume traces the logic of management development as related to the processes of industrial growth and analyzes management in three different ways: first as an economic resource, second as a system of authority, and third as a class or elite.
Includes index.
rua 20/10/16
Loans
Keywords: Industrial management